Thromboinflammatory Functions of Platelets in Ischemia–Reperfusion Injury and Its Dysregulation in Diabetes - Maiocchi, Sophie; Alwis, Imala; Wu, Mike Chia Lun; Yuan, Yuping; Jackson, Shaun P. (Seminars in Thrombosis and Hemostasis, 2018)
Ischemia–reperfusion (IR) injury is a common complication of a variety of cardiovascular diseases, including ischemic stroke and myocardial infarction (MI). While timely re-establishment of blood flow in a thrombosed artery is the primary goal of acute therapy in these diseases, paradoxically, reperfusion of ischemic tissue can cause widespread microvascular dysfunction that significantly exacerbates organ damage. Reperfusion injury is associated with activation of the humoral and cellular components of the hemostatic and innate immune systems and also with excessive reactive oxygen species production, endothelial dysfunction, thrombosis, and inflammation. Platelets are critical mediators of thromboinflammation during reperfusion injury and a hyperactive platelet phenotype may contribute to an exaggerated IR injury response. This is particularly relevant to diabetes which is characteristically associated with hyperactive platelets, significantly worse IR injury, increased organ damage, and increased risk of death. However, the mechanisms underlying vulnerability to IR injury in diabetic individuals is not well defined, nor the role of “diabetic platelets” in this process. This review summarizes recent progress in understanding the role of platelets in promoting microvascular dysfunction and inflammation in the context of IR injury. Furthermore, the authors discuss aspects of the thromboinflammatory function of platelets that are dysregulated in diabetes. They conclude that diabetes likely enhances the capacity of platelets to mediate microvascular thrombosis and inflammation during IR injury, which has potentially important implications for the future design of antiplatelet agents that can reduce microvascular dysfunction and inflammation.
Keywords: platelets; thromboinflammation; diabetes; ischemia–reperfusion injury